Attributions and paradoxes of agency in socially sustainable development : perspectives from small-scale NGOs in Jinja, Uganda - Kärkkäinen, Anna (2014)
During the past decades, sustainable development has become an important phenomenon in the global development discourse. The concept has been widely used by both large international bodies such as the United Nations as well as small grassroots organization. In the beginning, the interest was mainly in questions of environmental and ecological aspects of the concept but especially since the introduction of the Human Development Approach the importance of social and cultural aspects of sustainable development became more important. In the discussions on Human Development and sustainable development, the people are in the center of the discussion. Both concepts emphasize the importance of agency, both for individuals and for communities.